Respostas

A melhor resposta!
2014-06-02T17:27:43-03:00
 x4  - x²  = 3x² + 25
     6
 x4  - x²  = (3x² + 25).6
 x4  - x²  = 18x² + 150
 x4  - x²  - 18x² - 150 = 0
 x4  - 19x² - 150 = 0

Equação Biquadrada:
Para resolver você substitui o x4 = y² e o x² = y, ai você terá:

y²  - 19y - 150 = 0

Agora é só resolver pela fórmula de Báskara:

x = - b +- √b² - 4.a.c
              2.a
x = - (-19) +- √(-19)² - 4.(1).(-150)
                      2.(1)
x = - (-19) +- √361 + 600
                      2
x = - (-19) +- √961
               2
x = - (-19) +- 31
             2
x' = + 19 + 31  =  50  -----> x' = 25
            2             2
x" = + 19 - 31  -12   -----> x" = -6
            2             2

x = (25 , -6 )
1 5 1